2021
DOI: 10.3390/jpm11070589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid on Differentiation, Secretome and Stemness of Stem Cells from Human Exfoliated Deciduous Tooth (SHEDs)

Abstract: Stem cells from human exfoliated deciduous teeth (SHEDs) are considered a type of mesenchymal stem cells (MSCs) because of their unique origin from the neural crest. SHEDs can self-renewal and multi-lineage differentiation with the ability to differentiate into odontoblasts, osteoblast, chondrocytes, neuronal cells, hepatocytes, adipocytes, etc. They are emerging as an ideal source of MSCs because of their easy availability and extraordinary cell number. Ascorbic acid, or vitamin C, has many cell-based applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…In the present study, significant amounts of SDF‐1 and VEGF released by the scaffold and both factors were detected during all experimental times until 28 days. However, VEGF continued with increasing release rates (similar to Luminex assay), while SDF‐1 stabilized after 48 h. Studies that evaluated the composition of SHED‐secretome showed that VEGF is in greater quantity than SDF‐1, which justifies its increasing release pattern for a longer time, and was what we observed in the Luminex assay as well, with VEGF being one of the most abundant factors released (Bhandi et al., 2021).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, significant amounts of SDF‐1 and VEGF released by the scaffold and both factors were detected during all experimental times until 28 days. However, VEGF continued with increasing release rates (similar to Luminex assay), while SDF‐1 stabilized after 48 h. Studies that evaluated the composition of SHED‐secretome showed that VEGF is in greater quantity than SDF‐1, which justifies its increasing release pattern for a longer time, and was what we observed in the Luminex assay as well, with VEGF being one of the most abundant factors released (Bhandi et al., 2021).…”
Section: Discussionsupporting
confidence: 79%
“…However, a later study revealed that the molecules secreted by hDPSCs and SHEDs into the conditioned medium (CM) showed a bioactive function and regenerative ability [ 12 , 13 , 35 ]. As with BMMSCs, different proteins can be released by hDPSCs and SHEDs in the CM or inside the EVs [ 12 , 35 , 53 , 72 ].…”
Section: Secretome Of Dental Pulp Mscs and Their Biological Effectmentioning
confidence: 99%
“…Secreted neuroprotective factors may bind to specific receptors and trigger the activation of certain signalling pathways that coordinate cell function and survival [ 111 ]. In an in vitro model of PD, the SHED-CM demonstrated neuroprotective effects enhancing neurite outgrowth and repressed 6-hydroxydopamine-induced cell death [ 72 ]. Similarly, the SHED-CM showed a positive outcome in a PD rat model [ 108 , 112 , 113 ].…”
Section: Dscs Secretome In Central Nerve System Diseases Therapymentioning
confidence: 99%
“…Ascorbic acid treatment of SHEDs increased the release of growth factors necessary for the tissue regeneration and homeostasis, including VEGF, SCF, IGF-1, HGF, bFGF, Ang-1, and EGF, and anti-inflammatory cytokines, such as NO, indoleamine 2,3-dioxygenase (IDO), PGE-2, IL-10, and IL-6. On the contrary, inflammatory cytokines CCL2 and TGF-β1 were reduced [ 51 ].…”
Section: Mscs Secretomementioning
confidence: 99%